Aryl Sulfonium Salts for Site‐Selective Late‐Stage Trifluoromethylation. Issue 41 (4th September 2019) - Ye, Fei; Berger, Florian; Jia, Hao; Ford, Joseph; Wortman, Alan; Börgel, Jonas; Genicot, Christophe; Ritter, Tobias
Abstract: Incorporation of the CF3 group into arenes has found increasing importance in drug discovery. Herein, we report the first photoredox‐catalyzed cross‐coupling of aryl thianthrenium salts with a copper‐based trifluoromethyl reagent, which enables a site‐selective late‐stage trifluoromethylation of arenes. The reaction proceeds with broad functional group tolerance, even for complex small molecules on gram scale. The method was further extended to produce pentafluoroethylated derivatives. Abstract : Save the best for last : A site‐selective late‐stage trifluoromethylation of arenes proceeds via aryl sulfonium salts. The reaction features broad functional group tolerance and also enables the generation of C2 F5 derivatives of drug‐like compounds.